Traceability Supply Chain and Tuna Fishery Marketing Margin in Ocean Fishery Port (PPS) Kutaraja Lampulo, Banda Aceh City - Ranggayoni, Nanda Putri; Rizal, Muhammad; Munandar, Munandar; Hasanah, Uswatun; Mukhtarida, Mukhtarida (Universitas Teuku Umar, 2024)
Tuna fisheries represent a strategic sector within Indonesia’s fishing industry, offering high economic value and significant export potential. This study aims to analyze the traceability system of the supply chain and marketing margins of tuna fisheries at the Ocean Fishery Port (PPS) Kutaraja, Banda Aceh. A survey method was employed to collect data through structured interviews using purposive sampling. The findings reveal that the tuna supply chain involves multiple actors, from fishermen and local traders (toke bangku) to processing factories and exporters. The highest marketing margin, reaching 20%, was found at the processing level. The implementation of traceability systems is not yet fully integrated, particularly in the distribution and processing stages. Gap analysis indicates significant discrepancies between export traceability standards and current practices at PPS Kutaraja. Integrated policies to strengthen traceability systems, provide compliance incentives, and develop cold chain infrastructure are essential to enhance the competitiveness of Indonesian tuna exports and improve the welfare of local fishermen